2021
DOI: 10.1021/acsaem.1c02156
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Viologen–Cyclodextrin Electrolytes for Aqueous Organic Redox Flow Batteries

Abstract: Along with a primary modification of redox active materials, an additional introduction of secondary noncovalent interactions can synergistically enhance bulk properties of electrolytes for redox flow batteries. Herein, we highlight the host–guest complex formation between tailored viologens and highly water soluble (2-hydroxypropyl)-β-cyclodextrin as a key electrolyte interaction to modulate relevant electrochemical properties of aqueous redox flow batteries (AORFBs). The cyclodextrin-modified AORFB anolytes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 73 publications
0
11
0
Order By: Relevance
“…Upon protonation of a pyridine-containing polyaromatic heterocycle, one would expect to see an overall downfield shift of pyridyl proton signals in conjugation with the pyridinium ring due to the enhanced electron-accepting power of the pyridinium cation . One would also expect that the protons on the pyridinium would experience a stronger downfield shift due to the proximity of the pyridinium N atom pulling electron density away from the rest of the ring’s π cloud . We dissolved 5 in d 6 -DMSO because of its low-ppm solvent resonance and enhanced solubility of 5 over other polar aprotic solvents and added either one or two molar equivalents of triflic acid to protonate one or two pyridine N atoms (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Upon protonation of a pyridine-containing polyaromatic heterocycle, one would expect to see an overall downfield shift of pyridyl proton signals in conjugation with the pyridinium ring due to the enhanced electron-accepting power of the pyridinium cation . One would also expect that the protons on the pyridinium would experience a stronger downfield shift due to the proximity of the pyridinium N atom pulling electron density away from the rest of the ring’s π cloud . We dissolved 5 in d 6 -DMSO because of its low-ppm solvent resonance and enhanced solubility of 5 over other polar aprotic solvents and added either one or two molar equivalents of triflic acid to protonate one or two pyridine N atoms (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…143 In 2021, Cekic-Laskovic, Ravoo, Winter, and coworkers prepared viologen derivatives to construct host–guest complexes with highly water-soluble (2-hydroxypropyl)-β-cyclodextrin and employed them as electrolytes for aqueous redox flow AORFBs batteries. 144 The electrochemical performance of the AORFBs batteries was effectively improved by using the viologen moiety and cyclodextrin with excellent redox properties.…”
Section: Viologen-based Nanocompositesmentioning
confidence: 99%
“…In comparison, β-cyclodextrin (β-CD) features a larger cavity and can accommodate bigger hydrophobic molecules. Xu applied the host–guest inclusion strategy to assemble the reduced form of ferrocene into (2-hydroxypropyl)-β-cyclodextrin to increase its aqueous solubility. Cekic-Laskovic , used the same host to assemble a viologen derivative for the battery’s application. It was found that the complex yielded a negative shift in the redox potential of the viologen and an increase in the radicals’ stability against the dimerization, benefiting the AFB’s operation.…”
Section: Introductionmentioning
confidence: 99%